Ixora fulgida - Tsen, S.; Felix, E. C.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Ixora fulgida is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 120 km2 and 54,978 km2, respectively. It is widespread across the state and occurs in at least 11 protected areas in Sabah with no major threat to its population. It is assessed as Least Concern. Ixora fulgida is endemic to Sabah, Malaysia. It is widespread across the state